User talk:PaoloMartini

From HaskellWiki
Revision as of 15:44, 14 September 2006 by PaoloMartini (talk | contribs)
Jump to: navigation, search

Show that if p(x) is a polynomial of degree n, then p(x - 1) is a polynomial of the same degree.

Definition of polynomial.

p(x) = \sum_{i=0}^n a_i x^i

Binomial theorem.

(a + b)^n = \sum_{i=0}^n {n \choose i} a^{n-i} b^i

Special case.

(x - 1)^n = \sum_{i=0}^n {n \choose i} x^{n-i} (-1)^i

Binomial coefficient simmetry.

{n \choose k} = {n \choose n-k}

Hence:

(x - 1)^n = \sum_{i=0}^n {n \choose i} x^i (-1)^i
p(x-1) = \sum_{i=0}^n a_i (x - 1)^i
= \sum_{i=0}^n (a_i \sum_{k=0}^n {n \choose k} x^k (-1)^k).

zZzZ...